Review of National Text-Book “Pediatrics” for the students of higher medical educational establishments of the ІІІ-ІV levels of accreditation on specialty “Dentistry”. - O. P. Volosovets (Medičnì Perspektivi)
Review of National Text-Book “Pediatrics” for the students of higher medical educational establishments of the ІІІ-ІV levels of accreditation on specialty “Dentistry”.